3.-Facundo, el folletín en El Progreso (mayo - junio 1845) de Domingo Faustino Sarmiento - Hachim Lara, Luis; Hurtado Ruiz, Pablo (Nueva Revista del Pacífico, 2020)
Mediante la diferenciación entre folletín Facundo y el libro Civilización i barbarie, se analiza el rol que tuvo la ficción en la obra de Domingo Faustino Sarmiento. Se establece que el folletín contribuye a la narración melodramática de las consecuencias de la anarquía y barbarie, producto de la ignorancia del mestizo y del indígena frente al proyecto criollo que valoró, a su modo, la modernización europea como modelo y que tiene a Sarmiento como principal promotor. Abstract: By making a distinction between the newspaper serial Facundo and the book Civilización i barbarie, this work analyzes the role fiction had in the works of Domingo Faustino Sarmiento. The essay establishes the newspaper serial’s contributions to the melodramatic narrative. The narrative of the consequences of anarchy and barbarism is the byproduct of ignoring the Mestizo and the Indigenous vis à vis the Creole Project. The Creole Project values, in its own particular way, the European modernity as a model with Sarmiento as its main advocate.